THE EFFECT OF GOOD CORPORATE GOVERNANCE, FIRM SIZE AND FINANCIAL LEVERAGE ON INCOME SMOOTHING AND ITS IMPLICATION ON STOCK RETURN - Cahyani Putri, Wulandari (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
This study aims to analyze the effect of good corporate governance, company size and financial leverage on income smoothing and it?s implication on stock returns. The study population was 555 companies listed on the Indonesia Stock Exchange for the period 2011-2015, by using the purposive sampling method, obtained 40 companies. The analysis method uses penel data and Eviews 9.0 software. The research method used is quantitative by using secondary data, namely the company's annual financial statements. The results of the analysis show that good corporate governance, company size and financial leverage simultaneously have a significant effect on income smoothing. Partially, good corporate governance-independent commissioners and financial leverage have a positive and significant effect on income smoothing. But the variable size of the company has a negative effect and is significant for income smoothing. While income smoothing has a negative and significant effect on stock returns.